1997
DOI: 10.1074/jbc.272.49.30693
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase Activity Is Necessary for Insulin-dependent Inhibition of Apolipoprotein B Secretion by Rat Hepatocytes and Localizes to the Endoplasmic Reticulum

Abstract: Insulin inhibits apolipoprotein B (apoB) secretion by primary rat hepatocytes through activation of phosphoinositide 3-kinase (PI 3-K). Current studies demonstrate that the PI 3-K inhibitor wortmannin inhibits both basal and insulin-stimulated PI 3-K activities. Wortmannin and LY 294002, two structurally distinct PI 3-K inhibitors, prevent insulin-dependent inhibition of apoB secretion in a dose-dependent manner.To link PI 3-K activation to insulin action on apoB, we investigated whether insulin induced locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 68 publications
3
104
1
Order By: Relevance
“…The interface between PI3K-dependent signaling and apoB assembly and secretion is not known in detail, although in some studies, insulin-mediated signaling, via PI3K and Akt, regulates MTP expression and, hence, VLDL particle number and size (18,29,31,32). Although MTP is the target for some forms of PI3K-mediated regulation of VLDL assembly (32), MTP expression was unaffected by ABCA1 deficiency in this study (Fig.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…The interface between PI3K-dependent signaling and apoB assembly and secretion is not known in detail, although in some studies, insulin-mediated signaling, via PI3K and Akt, regulates MTP expression and, hence, VLDL particle number and size (18,29,31,32). Although MTP is the target for some forms of PI3K-mediated regulation of VLDL assembly (32), MTP expression was unaffected by ABCA1 deficiency in this study (Fig.…”
Section: Discussioncontrasting
confidence: 39%
“…The current studies demonstrate that VLDL from HSKO mice is more buoyant and of larger diameter than that of WT mice, which is also consistent with ABCA1/PI3K exerting effects during the second step of VLDL assembly. Because PI3K is present in the endoplasmic reticulum and Golgi, is involved in intracellular vesicular trafficking, and is increased with insulin stimulation (29,35,36), we hypothesize that the lack of ABCA1 in hepatocytes and the resultant attenuation of PI3K activation results in slower VLDL transit through the secretory pathway, allowing additional time for second step VLDL particle expansion. This hypothesis is supported by the observations of defective lipid and vesicular trafficking from the Golgi to the plasma membrane in fibroblasts from TD subjects (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the signal responsible for targeting apoB-containing lipoproteins in cells incubated with ⍀-3 fatty acids is established before the particles exit from the ER and serves to trigger the appropriate trafficking of the doomed substrate to post-ER degradation. Along these lines, it has been suggested that insulin-stimulated apoB degradation in rat primary hepatocytes involves PI3K translocation to the ER membrane and the sorting of apoB to a post-ER degradative pathway (51).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently observed that brefeldin A also protects apoB from acute insulin-stimulated degradation in rat primary hepatocytes (50), a process that depends on PI3K activation (50,51). Therefore, to determine if similar signaling is also involved in the effects of ⍀-3 fatty acids, we treated rat primary hepatocytes for 5 h, in the absence or presence of the PI3K inhibitor wortmannin (1 M), with BSA alone or BSA complexed with DHA or OA.…”
Section: Relationship Between ⍀-3 Fatty Acid-induced Degradationmentioning
confidence: 99%
“…The EGF-induced phosphorylation of IRSs was accompanied by activation of PtdIns 3-kinase via binding of p85, the regulatory subunit of the enzyme, to the phosphorylated IRSs. In view of the pivotal role of PtdIns 3-kinase in a variety of intracellular signalling cascades [11,19], IRS-1 and IRS-2 must be important members in EGFR-initiated signalling pathways in cultured hepatocytes.…”
Section: O N C L U S I O N Smentioning
confidence: 99%